Cognitive dissonance induction as an “inoculator” against negative attitudes towards victims - Barriga, P. (2022)
The “belief in a just world” and the related “justice motive” can be construed as a fundamental drive-in people's life. Paradoxically this “justice motive” may motivate people to be unfair by assigning blame to objectively innocent victims. In two experimental studies, we address the possibility that inducing cognitive dissonance can reduce the assigning of blame to innocent victims. Study 1 (n = 71) consisted of a 2 × 2 design in which participants were randomly assigned to two types of induction (Dissonance induction/Awareness Induction Only condition) and two victims' background conditions (innocent victim v non-innocent victim). In Study 2 (n = 171) 3 types of induction were compared (Dissonance Induction/Awareness Induction/Control condition) with all victims' scenarios considering them innocent. Study 1 showed that innocent victims were less negatively evaluated in the Dissonance Induction condition compared to the Awareness Only Induction condition; non-innocent victims were not differently evaluated in both conditions. Study 2 showed that innocent victims were less negatively evaluated in the Dissonance Induction condition compared to the Awareness Induction condition and the Control condition. Overall, findings suggest that cognitive dissonance induction can be an effective mechanism to reduce assigning blame to innocent victims.